Model Pemerintahan Dunia: Perspektif Taqyuddin An Nabani - Muslikhati, Siti (Jurnal Hubungan Internasional, 2012)
This paper aims to analyze the idea of world government by using Taqyuddin An Nabhaniâs perspective. It argues that, according to Nabhani, a world government has its rooted on ideological belief system. For Nabhani, the final form of world systems can be understood based on Islam as an ideology. Historically, Islam as a political ideology has run a genuine system called Khilafah Islamiyah.